The Holy City a novel - McCabe, Pat 1955- (Bloomsbury, 2009)
Chris McCool, a dandyish, debonair playboy, a product of the wealthy Protestant wife of another man, and a poor Catholic farmer, reflects on his two lives--the one he lives and the darker one he is capable of and tries to forget.